Ion temperature measurements in the tokamak scrape-off layer with high temporal resolution. (15th February 2021) - Adamek, J.; Cipciar, D.; Devitre, A.; Horacek, J.; Cavalier, J.; Komm, M.; Krbec, J.; Tichy, M.; Trunec, D.; Böhm, P.; Panek, R.; team, the COMPASS
Abstract: We present a uniquely fast (10 μ s) ion temperature measurements in the tokamak edge plasma. Our approach is based on the sweeping of a ball-pen probe, where the ion temperature is obtained by fitting the electron branch of the corresponding I – V characteristic. We have performed measurements on the COMPASS tokamak during L-mode discharge. The temperature histograms reveal a non-Gaussian shape with a high-temperature tail peaking at low values. The fitted values of fast I – V measurements can be used to reconstruct (emulate) the slow swept I – V characteristic of a retarding field analyzer. The resulting ion temperature profile is nearly flat and provides a ratio of ion to electron temperature close to 1–2 in the vicinity of the last closed flux surface during L-mode discharges, as observed on other tokamaks.